Analisis Yuridis Sebab Wakaf Tidak Dapat Dibatalkan Dalam Perspektif Putusan Pengadilan Agama - Fitri, Al (Legalita, 2025)
One form of legal act of a person or legal entity is called wakif. It is separating or handing over part of his property to be used and institutionalized forever or for a certain period of time according to his interests for the purposes of worship or public welfare, therefore wakif cannot be canceled. The purpose of this study is to determine the legal reasons so that wakif cannot be canceled from the perspective of the Religious Court's decision. This topic is interesting to study further even though the regulations are clear. There are still lawsuits for the cancellation of wakif that reach the legal realm. This research method uses a formal legal approach with analytical descriptive specifications. The source of research data was obtained from primary and secondary legal materials with data collection techniques from various libraries and literature studies. Data presentation is through descriptive, and the author's analysis method is through qualitative analysis. The results of the study indicate the need for the principle of legal certainty in wakif because wakif no longer has a legal bond with the wakif and returns to being the right of Allah SWT, and the wakif is not included as a legal subject in a lawsuit for the cancellation of wakif. The contribution of this study is to analogize wakif with a grant, by revoking or canceling a waqf. The law of canceling a waqif includes acts that are not permitted.